Please help simplify the second question
![Please help simplify the second question class=](https://us-static.z-dn.net/files/da8/708ac69390caf850b09890b15ec92b30.png)
Answer:
[tex]\frac{3x}{(x-3)(x+1)}[/tex]
Step-by-step explanation:
[tex]\frac{2x-1}{x^2-2x-3}[/tex] + [tex]\frac{1}{x-3}[/tex]
= [tex]\frac{2x-1}{(x-3)(x+1)}[/tex] + [tex]\frac{1}{x-3}[/tex]
multiply the numerator/ denominator of 2nd fraction by (x + 1)
= [tex]\frac{2x-1}{(x-3)(x+1)}[/tex] + [tex]\frac{x+1}{(x-3)(x+1)}[/tex]
add the numerators , leaving the common denominator
= [tex]\frac{2x-1+x+1}{(x-3)(x+1)}[/tex]
= [tex]\frac{3x}{(x-3)(x+1)}[/tex]
Answer:
A) (x+1)(x-3)
B) 3x / x^2 - 2x - 3
or (3x ÷ x^2 - 2x - 3)
Hope this helps!